IMPROVING STUDENTS’ WRITING SKILL THROUGH MIND MAPPING TECHNIQUE AT MA AL-FATWA SUGAI RAYA - Abdul Mukib; Muhammad Yassin; Dewi Ismu Purwaningsih (English Language Teaching Journal, 2023)
This study was conducted to improve the students’ writing skill through mind mapping technique of the eleventh graders at MA Al-Fatwa. As stated in statement of research problem ‘’ How can students’ writing skill of descriptive text be improved through mind mapping technique’’ Furthermore, this study employed a Classroom Action Research method. This research was conducted based on Kemmis & Mc Taggert, (1988) model, there are; planning, acting, observing, and reflecting. The research was also carried out in two cycles. In data collecting, the researcher used three kind of instruments, there were; test, questionnaire and observation checklist. The result of the research on the cycle 1 showed that the average scores on students’ writing skills were 70. On other hand, the average scores on students’ writing skills were still below the KKM, it is 75. The result on students’ writing skill on the cycle 2 were 78.18. While, there were 27.2% of students who did not pass the KKM. It was also proved by the result on students’ perception and students’ behavioral changes during classroom process. The students got joyful classroom atmosphere during the lesson. It can be assumed that students’ writing skill can be improved through mind mapping technique